An alternative assessment for transit-oriented developments (TODs) with land use/land cover (LULC) - Yildirim, Yalcin; Akin, Anil (Springer, 2023)
Cities experience rapid growth, and various drivers shape this growth. Notably, developing countries experience challenges on land use and transportation conflict. The idea of transit-oriented developments (TODs) is a solution for this concern of urbanization while there is no consensus on defining and identifying them. This study concentrated on the dynamics of land use/land cover (LULC) effects on transit-oriented developments (TODs) by utilizing light rail stations from a metropolitan area in Turkey, as this is the first attempt in this geography. Spatial data covers of high-resolution Sentinel 2A remotely sensed data and Google Earth images acquired in 2021. The study performed the analyses within a 500-m light rail train station buffer. The results reveal that TODs include more urbanized, open space, street connection, commercials, and dense population as expected from the TOD concept. Local officials, practitioners, and developers should be involved with the TOD implementation and policy phases to establish tangible developments in urbanization.
Keywords: TODs; Urbanization; Rail transit; Planning; LULC